TACE-Sorafenib With Thermal Ablation Has Survival Benefits in Patients With Huge Unresectable Hepatocellular Carcinoma - Wu, Ying; Qi, Han; Cao, Fei; Shen, Lujun; Chen, Shuanggang; Xie, Lin; Huang, Tao; Song, Ze; Zhou, Danyang; Fan, Weijun (Frontiers in Pharmacology, 2020)
Purpose To investigate the effectiveness and safety of transarterial chemoembolization (TACE) combined with sorafenib and thermal ablation in patients with huge hepatocellular carcinoma (HCC). Materials and Methods This retrospective study examined 50 patients with huge unresectable HCC treated from January 2009 to December 2015. Among them, 28 cases received TACE-sorafenib treatment (TACE-sorafenib group), and 22 cases received TACE-sorafenib plus thermal ablation treatment (TACE-sorafenib-thermal ablation group). The Overall survival (OS), progression-free survival (PFS), and adverse events (AEs) were compared. Results The median follow-up was 13.5 months (ranges 4.2 to 96.7 months). The median OS was significantly longer in the TACE-sorafenib-thermal ablation group than that in the TACE-sorafenib group (20.8 vs. 10.4 months, P=0.003). The median PFS of the ablation and no ablation groups were 4.3 vs. 7.1 months (P=0.546). The treatment modality was an independent predictor of OS (P=0.004). There were no notable drug-related high grade adverse events or permanent adverse sequelae. Conclusion TACE-sorafenib-thermal ablation provided extended OS to patients with huge unresectable HCC and could be a better choice than TACE-sorafenib.